(untitled) (Acta Scientiarum. Biological Sciences, 2024)
Obesity is a chronic disease related to gastrointestinal disorders. Pterostilbene has already demonstrated beneficial activity. This study aimed to evaluate the effects of a sucrose-rich diet and pterostilbene on oxidative status, intestinal wall, and myenteric neurons of the jejunum. Wistar rats comprised the groups Control (C), Sucrose (S), Control+Pterostilbene (CP), and Sucrose+Pterostilbene (SP). For 180 days, C and CP received water and chow ad libitum, while S and SP groups received chow and water plus 40% sucrose ad libitum. Pterostilbene (40 mg Kg-1) was administered daily in the final 40 days. Jejunal samples were collected to assess oxidative status, wall morphometry, goblet cells, and myenteric neurons. Pterostilbene increased lipid peroxidation in the CP group. Catalase activity increased in groups S and CP. The myenteric neuron number did not change by sucrose; however, it reduced their number in CP. SP animals had a higher density of neurons than CP. Groups S, CP, and SP showed hypertrophy of the neuronal cell body. There was maintenance of the intestinal wall and goblet cells. In conclusion, pterostilbene has a possible pro-oxidant and cytotoxic activity on jejunal myenteric neurons of rats on a standard diet; however, when combined with 40% sucrose-added water, it minimized the oxidative stress, evidencing a neuroprotection activity.